Association between composite dietary antioxidant index and hyperlipidemia: a cross-sectional study from NHANES (2005–2020) - Minli Zhao; Danwei Zhang; Qiuping Zhang; Yuan Lin; Hua Cao (Scientific Reports, 2024)
Abstract The association between the composite dietary antioxidant index (CDAI) and hyperlipidemia remains unclear. Therefore, this study aimed to investigate the relationship between CDAI and hyperlipidemia. The data used in this study were obtained from the National Health and Nutrition Examination Survey (NHANES) dataset spanning from 2005 to 2020. Based on 24-h dietary recall interviews, the CDAI was calculated using the intake of six dietary antioxidants. Univariate and multivariate logistic regression models were employed to investigate the relationship between CDAI and the occurrence of hyperlipidemia. Additionally, restricted cubic spline (RCS) analysis was utilized to investigate potential non-linear relationships between the CDAI and risk of hyperlipidemia. The final analysis included 30,788 adults in the United States, among whom 25,525 (82.91%) were diagnosed with hyperlipidemia. A significant negative correlation was observed between the CDAI and hyperlipidemia in the unadjusted (Odds ratio [OR] 0.97 [95% CI 0.96, 0.98]) and multi-variable adjusted (OR 0.98 [95% CI 0.97, 0.99]) models. When the CDAI values were analyzed as a categorical variable, individuals in the highest quartile (OR 0.82 [95% CI 0.73, 0.92]) exhibited a nearly one fifth decreased risk of hyperlipidemia compared to those in the lowest quartile. Additionally, RCS analysis revealed a linear relationship between CDAI and hyperlipidemia (P for nonlinearity = 0.124). The results remained consistent across subgroups except for individuals under the age of 60 or those with diabetes mellitus. There was a significant negative correlation between the CDAI and risk of hyperlipidemia, indicating that maintaining an optimal CDAI level could effectively reduce the incidence of hyperlipidemia.